Gram‐Scale Synthesis and Highly Regioselective Bromination of 1, 1, 9, 9‐Tetramethyl[9](2, 11)teropyrenophane. Issue 6 (16th January 2018) - Unikela, Kiran Sagar; Roemmele, Tracey L.; Houska, Václav; McGrath, Kaitlin E.; Tobin, David M.; Dawe, Louise N.; Boeré, René T.; Bodwell, Graham J.
Abstract: An improved synthetic pathway to the nanobelt‐like 1, 1, 9, 9‐tetramethyl[9](2, 11)teropyrenophane has been developed, and enables the synthesis of gram quantities of material. Key innovations are the development of a sequential chlorination/Friedel–Crafts alkylation reaction, a sequential iodination/Wurtz coupling reaction, and a room‐temperature teropyrene‐forming reaction. The teropyrenophane was found to form a very stable radical cation and undergo a completely regioselective fourfold bromination reaction. Abstract : Go big or stay home ! The title compound can now be synthesized on a gram scale by an improved synthetic pathway. The EPR spectroscopy of its radical cation provides a rationale for the completely regioselective fourfold bromination of the severely bent teropyrene system.